2021
DOI: 10.1177/11786221211021395
|View full text |Cite
|
Sign up to set email alerts
|

A Soil Water Assessment Tool (SWAT) Modeling Approach to Prioritize Soil Conservation Management in River Basin Critical Areas Coupled With Future Climate Scenario Analysis

Abstract: About 44% of the Indian landmass experiences the adverse impact of land degradation. This loss of sediments caused by soil erosion reduces the water quality of local water bodies and decreases agricultural land productivity. Therefore, decision-makers must formulate policies and management practices for sustainable management of basins that are cost-effective and environment friendly. Application of the best management practices (BMPs) to properly manage river basins is difficult and time-consuming. Its implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…BeOH was oxidized by ignition in a quartz crucible at 800 • C for 10 min [59]. BeO was then mixed with Nb metal and loaded onto targets for the measurement of the 10 Be/ 9 Be ratio by the 6MV accelerator mass spectrometer (AMS) at the facility of the Korean Institute of Science and Technology (KIST), Seoul, Korea [59]. Isotope ratios were normalized to the 10 Be standards [60], and the measured isotope ratios were converted to cosmogenic 10 Be concentrations in quartz using the total 10 Be in the samples and sample weights.…”
Section: Natural Background Sediment Yield Derived From 10 Bementioning
confidence: 99%
See 2 more Smart Citations
“…BeOH was oxidized by ignition in a quartz crucible at 800 • C for 10 min [59]. BeO was then mixed with Nb metal and loaded onto targets for the measurement of the 10 Be/ 9 Be ratio by the 6MV accelerator mass spectrometer (AMS) at the facility of the Korean Institute of Science and Technology (KIST), Seoul, Korea [59]. Isotope ratios were normalized to the 10 Be standards [60], and the measured isotope ratios were converted to cosmogenic 10 Be concentrations in quartz using the total 10 Be in the samples and sample weights.…”
Section: Natural Background Sediment Yield Derived From 10 Bementioning
confidence: 99%
“…The treatment repeatedly etches minerals in a dilute HF/HNO3 mixture [58]. We added a 9 Be carrier with a 10 Be/ 9 Be ratio < 3.0 ×10 −15 , then separated and purified the Be by ion exchange chromatography and selective precipitation of BeOH at pH > 7. BeOH was oxidized by ignition in a quartz crucible at 800 °C for 10 min [59].…”
Section: Natural Background Sediment Yield Derived From 10 Bementioning
confidence: 99%
See 1 more Smart Citation
“…This model has some uncertainties related to the physical and conceptual parameters, drainage area, HRUs (hydrologic response unit), and elevation band (Shen et al ., 2012). To cope with those uncertainties, high‐level precision of the sensitivity analysis, calibration, and validation are needed (Himanshu et al ., 2017; Bhatta et al ., 2019; Dayal et al ., 2021; Pandey et al ., 2021). Therefore, this study aims to project the future streamflow by using this model with possible high performance using the required number of subbasins, HRUs, and elevation bands.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the SWAT model is robust and suitable for evaluating the effectiveness of land-use changes and land management practices as well as best agricultural management practices on small and large watershed scales. Several studies carried out in Thailand and in other regions have similarly reported the success of SWAT in evaluating the impact of land management practices on streamflow and sediment [16,[63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%